2012
DOI: 10.1111/j.1365-3040.2012.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

The reorganization of actin filaments is required for vacuolar fusion of guard cells during stomatal opening in Arabidopsis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Monitoring the dynamic changes in guard cell vacuolar structures revealed an intense remodeling during stomatal movements (11,12). Pharmacological and genetic approaches indicated that dynamic changes of the vacuole are crucial for achieving the full amplitude of stomatal movement (12)(13)(14). However, so far, no specific tonoplast transport proteins or processes have been functionally linked to vacuolar dynamics during guard cell movements.…”
mentioning
confidence: 99%
“…Monitoring the dynamic changes in guard cell vacuolar structures revealed an intense remodeling during stomatal movements (11,12). Pharmacological and genetic approaches indicated that dynamic changes of the vacuole are crucial for achieving the full amplitude of stomatal movement (12)(13)(14). However, so far, no specific tonoplast transport proteins or processes have been functionally linked to vacuolar dynamics during guard cell movements.…”
mentioning
confidence: 99%
“…3), seemed to function separately, with the internal layer being linked to the tannin content and the external layer being attached to the cytoplasmic cytoskeleton (Fleurat-Lessard 1988). Indeed, the actin network is involved in the regulation of vacuole morphology, as shown by its disruption in Arabidopsis guard cells, which results in the inhibition of vacuole fusion during stomatal opening (Li et al 2012). However, the detailed mechanism of the manner by which actin affects transvacuolar strand formation, and vacuole fusion has not yet been elucidated (Zhang et al 2014).…”
Section: Distributions Of Double Vacuolar Apparatus In Various Sensitmentioning
confidence: 96%
“…Even in Arabidopsis, different cell types have an order-of-magnitude variation in filament elongation rates. For example, studies have found that guard cells and pollen have elongation rates of 0.3-0.7 μm/s (57,82,83,134), which, when balanced with disassembly at nearly equal rates, could be indicative of filament treadmilling. Similarly, in moss protonemal cells and Arabidopsis cotyledon or root epidermal cells, assembly and disassembly appear to be nearly equivalent (3,96).…”
Section: Variations On a Theme In Different Organisms And Cell Typesmentioning
confidence: 98%
“…In very few cases, however, have single-filament dynamics been evaluated quantitatively in these mutant plants. Guard cells from Arabidopsis arp2 and arp3 mutants have modest but significant increases in actin filament dynamics ( Table 2): Filament elongation and depolymerization rates are enhanced by as much as 40%, and the severing frequency is doubled (57). The reason for this is not clear, because the ARP2/3 complex is not known to sever filaments or bind G-actin, unless perhaps there is a shift in the ratio of F-to G-actin in arp2/3 mutant plants.…”
Section: Filament Initiation Needs To Be Interrogated Genetically Andmentioning
confidence: 99%
See 1 more Smart Citation